1995
DOI: 10.1001/archsurg.1995.01430110044008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α Gene Expression in Human Peritoneal Macrophages Is Suppressed by Extra-abdominal Trauma

Abstract: Human PM phi constitutively show high levels of TNF-alpha message expression, and this is down-regulated by polytrauma. This might constitute a functionally "primed" state. If so, TNF-alpha down-regulation might contribute to functional PM phi suppression after systemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Polymicrobial sepsis has been found to reduce the capacity of peritoneal macrophages to release proinflammatory cytokines in re- sponse to lipopolysaccharide (45). Clinically, Hauser et al (46) demonstrated that polytrauma significantly reduces TNF-␣ messenger RNA expression in peritoneal macrophages while simultaneously increasing IL-10 messenger RNA in PBMCs. This is even more remarkable because these data are corroborated by our findings of an increased IL-10 production in PBMCs associated with decreased production of proinflammatory mediators in peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Polymicrobial sepsis has been found to reduce the capacity of peritoneal macrophages to release proinflammatory cytokines in re- sponse to lipopolysaccharide (45). Clinically, Hauser et al (46) demonstrated that polytrauma significantly reduces TNF-␣ messenger RNA expression in peritoneal macrophages while simultaneously increasing IL-10 messenger RNA in PBMCs. This is even more remarkable because these data are corroborated by our findings of an increased IL-10 production in PBMCs associated with decreased production of proinflammatory mediators in peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory cytokines (e.g., IL-10 and transforming growth factor beta [TGF-beta]) are involved in the downregulation of the inflammatory response. For instance, IL-10 can deactivate macrophages; and the TNF levels in patients with trauma get higher when IL-10 levels are depressed, a scenario that has been implicated in the onset of septic complications [95]. TGF beta is a potent inhibitor of monocyte activation [96]; and significantly elevated levels of TGF beta have been observed in monocytes derived from immunosuppressed patients after trauma.…”
Section: Comparison Of Systemic Inflammation In Sepsis and Hemorrhagementioning
confidence: 99%
“…15 Another study demonstrated decreased TNF␣ mRNA levels in human peritoneal macrophages after polytrauma, while the antiinflammatory cytokine IL-10 was upregulated. 16 Taken together, these results suggest that the early innate immune response, as well as the adaptive immune response, to pathogens is attenuated in patients with TBI. However, the mechanism underlying this immune paralysis following brain injury remains unclear.…”
Section: Immune Paralysis In Patients With Tbimentioning
confidence: 81%